Proceso de atención nutricional en paciente masculino de 30 años de edad con virus de la inmuno deficiencia humana. - Carrillo Jacome, Andres Fernando (2022)
It is clear that HIV infection has no cure, even so, those individuals who unfortunately became infected could enjoy better health by maintaining a good nutritional status, a fact that represents a fundamental part for these people to maintain their health in the short and long term. Therefore, in the clinical case in question, it was proposed to lead a patient with HIV to improve their initial nutritional status, carrying out all the steps involved in a nutritional care process, thus including in its development its four steps, which correspond to the nutritional assessment through the collection and interpretation of anthropometric data using indices and indicators, biochemical parameters, physical assessment through the clinic and dietary through the analysis of their food consumption. Diagnosis, intervention or nutritional management and follow-up represent the remaining steps. We worked for a month with a male patient diagnosed with HIV, who is 30 years old. The results obtained show that a subtle improvement in their nutritional condition has been achieved compared to their anthropometric, biochemical, clinical and dietary data collected and analyzed initially. This concludes that achieving the improvement of nutritional status in patients with HIV turns out to be more complex than is really expected, but, even so, it is necessary to emphasize the role that nutrition plays for the good health of these patients.